Eptifibatide-induced acute profound thrombocytopenia: A case report. Issue 42 (21st October 2022) - Alamin, Mohammed A.; Al-Mashdali, Abdulrahman; Al Kindi, Dawoud I.; Elshaikh, Elkhansa A.; Othman, Fahmi
Abstract : Rationale: Eptifibatide is an antiplatelet agent used in the medical management of acute coronary syndrome. Although multiple studies did not reveal a significant association between eptifibatide and the development of thrombocytopenia, recent case reports brought attention to this relatively rare side effect. Patient concerns: We report a 61 years old male with acute coronary syndrome who underwent primary coronary intervention. Diagnosis and intervention: The patient developed acute profound thrombocytopenia following eptifibatide administration. Following prompt offending drug discontinuation, the platelet counts recovered, without clinical sequelae or the need for platelet transfusion. Dual antiplatelet therapy with aspirin and clopidogrel was resumed after platelet count normalization. Outcomes: The patient had a normal platelet count and no bleeding events on follow-up after three months upon discharge. Conclusion: Eptifibatide, a glycoprotein IIa/IIIb inhibitor used in the management of acute coronary syndrome, can induce acute, profound thrombocytopenia that can have significant morbidity in patients. This case highlights this relatively rare side effect and the importance of monitoring blood counts and observing for any signs of bleeding or thrombosis that might occur in such patients.